Social Forestry in Kerala State - Basha, S. Chand (Indian Forester, 1991)
The different Social Forestry activities taken up under the various programmes in Kerala have been discussed. The Involvement of people specially the Non-Governmental Organisations in the Farm Forestry sector has been given. The welfare activities benefiting Scheduled castes and Scheduled Tribes taken up under the Social Forestry Schemes have been mentioned. The distribution of produce to the deserving people and the procedure approved by the Government for dealing with the produce obtainable from the various plantations Including that of tribal sector are dealt with In brief. Civil works taken up for the effective Implementation of the World Bank Aided Social Forestry ProJect has been touched upon. The various research organisation Involved in conducting the research and the research activities taken up the various fields of social forestry are discussed. Special mention has been made on the publicity and extenalon activities Implemented.